Ancient Mysteries Lost cities Disc 2 - History Channel (Television network); Arts and Entertainment Network ([United States] : A & E Television Networks, 2011)
Includes Lost city of pirates and Machu Pichu: city in the sky.
Lost city of pirates -- Machu Pichu: city in the sky.
Title from container.
DVD; Dolby Digital stereo.
108180
Keywords: Teach, Edward, -- -1718.; Extinct cities; Pirates; Extinct cities -- Peru; Documentary television programs; Nonfiction television programs